Short Food Supply Chains as a Policy Tool for Smart and Sustainable Rural Development in the European Union - Panciszko-Szweda, Barbara (Studia Ecologiae et Bioethicae, 2025)
The article addressed issues related to the concept of rural development in the EU, namely smart villages. It is necessary to consider what instruments will contribute to the creation of smart villages in EU countries. The tool that was analysed in this paper is Short Food Supply Chains (SFSCs). The aim of this paper is to identify the common points between the features of SFSCs and the main components of smart villages. The author posited research hypothesis that SFSCs contribute to the development of smart villages in the EU. The main objective and research hypothesis required the use of qualitative research methods (critical literature analysis and comparative analysis). The first part of the article presents the definition of SFSCs in literature. Next, the author indicates the main features of SFSCs. The third part includes a short description of the history of implementing and supporting SFSCs by EU under rural development policy. Then, the concept of smart villages is presented. The author identified the areas that constitute the components of smart villages (smart economy, smart society, smart environment, smart agriculture, smart governance and smart accessibility). Next, the comparative method was used to identify common areas between smart villages and SFSCs concepts. The analysis shows that promoting and implementing SFSCs will lead to creating smart villages in the EU.